Control fisicoquímico de Clorfenamina 4 mg tabletas realizado en el laboratorio HYPATIA S.A., Lima, 2016 - 2017 - Burgos Aguilar, Martha Paola (2017)
The present report of pre-professional practices was aimed at performing the physico-chemical control of Chlorphenamine 4 mg tablets in the laboratory HYPATIA S.A. The sample consisted of 5 different batches of 200 tablets each, using a simple random sampling technique, obtained from a pharmaceutical industry, which were delivered to the counter sample area to be derived to the area of physicochemistry for its corresponding analysis. The results obtained from the analyzes were: appearance, round shaped tablet with central groove on one of its sides. Orange color with whitish and more intense orange color scores; for the mass uniformity test, resulting in 182.14 mg / tab; solution with 98.28%; content with a percentage of 102.3% and uniformity of content with a percentage of 6.84% (AV); the results obtained were within the values established by the official standard USP 39 and the technical standard of laboratory of origin. It is concluded that Chlorphenamine 4 mg Tablets comply with the specifications set forth by USP 39 and the technical standard of the laboratory of origin